2011
DOI: 10.1007/s10585-011-9397-5
|View full text |Cite
|
Sign up to set email alerts
|

Localization of sporadic neuroendocrine tumors by gene expression analysis of their metastases

Abstract: A characteristic of human gastroenteropancreatic neuroendocrine tumors (GEP-NET) is a minute unobtrusive primary tumor which often cannot be detected by common physical examinations. It therefore remains unidentified until the tumor has spread and space-occupying metastases cause clinical symptoms leading to diagnosis. Cases in which the primary cannot be located are referred to as NET with CUP-syndrome (cancer of unknown primary syndrome). With the help of array-CGH (comparative genomic hybridization, Agilent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 58 publications
2
28
1
2
Order By: Relevance
“…Other gene expression classifiers have included NETs where the primary sites were not verified by surgery. [26,27] The 92-gene classifier developed by Kerr et al relies on primary site determinations made by a central pathology adjudication committee. [26] Although they applied rigorous methods to define the primary site, inclusion of biopsy specimens without surgical confirmation of the presumed primary site introduces uncertainty into classifier development and validation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other gene expression classifiers have included NETs where the primary sites were not verified by surgery. [26,27] The 92-gene classifier developed by Kerr et al relies on primary site determinations made by a central pathology adjudication committee. [26] Although they applied rigorous methods to define the primary site, inclusion of biopsy specimens without surgical confirmation of the presumed primary site introduces uncertainty into classifier development and validation.…”
Section: Discussionmentioning
confidence: 99%
“…Posorski et al reported a three-gene expression signature for distinguishing gastrointestinal NETs, but this was based on expression measured in primary and metastatic NETs from only 17 patients, including samples from gastric, colonic, and unknown primaries in addition to PNETs and SBNETs. [27] Due to the low numbers of individual tumor types and lack of additional validation specimens, the value of this gene expression signature remains unproven. The much larger study by Kerr et al determined a 92-gene expression signature to classify cancers of unknown primary based on a database of 2094 tumors of all types and validated on 790 others, including 50 neuroendocrine tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This limitation can be partially overcome by laser-based tissue microdissection as it allows a more precise sample preparation for further molecular analysis [2]. However, tissue microdissection is a time consuming technique and highly sensitive downstream analyses are needed [2][3][4], due to the limited number of samples.…”
Section: Introductionmentioning
confidence: 99%
“…1 zeigt beispielhaft 2 FĂ€lle eines metastasierten Tumors des Ileums mit unterschiedlichen Genexpressionsprofilen. Der Fortschritt in den genetischen Untersuchungen wird jedoch bald neue Erkenntnisse zur Pathogenese der NET und ihrer Metastasen aufweisen, wie kĂŒrzlich exemplarisch von Posorski et al gezeigt, die nachwiesen, dass die Detektion von 3 Markergenen ausreicht, um den Ursprung der hĂ€ufigsten neuroendokrinen, primĂ€ren Tumorlokalisationen des Ileums und des Pankreas anhand der Genexpression zuverlĂ€ssig vorherzusagen [16].…”
unclassified